Criminal Policy on the Implementation of Penalties for Combating Sexual Violence in the Indonesian Criminal Law System - Sri Wahyuni Laia; Mompang Lycurgus Panggabean (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Sexual violence is a prevalent issue in various societies, transcending time and space, affecting environments such as family, education, community, professional, and social settings. The threat to vulnerable individuals, especially women, induces a universal sense of fear. Violence against women is not limited to physical acts or threats but also includes psychological and social harm. This study employs a legal sociology approach, a legislative approach, and a conceptual approach, with a descriptive research specification aimed at obtaining a complete picture or description of the prevailing legal conditions in a particular place, the existing legal phenomena, or specific legal events occurring in society. The primary data used in this research is obtained directly from informants or resource persons. Additionally, secondary data is used, consisting of primary legal materials, secondary legal materials, and tertiary legal materials, collected through literature studies as supporting data that provide explanations for the primary data. Data collection techniques include interviews and document studies, analyzed qualitatively. Historically, criminal policy concerning sexual violence within the Indonesian criminal law system has existed since Indonesia's independence and continues to this day. However, addressing the legal substance is not sufficient; its implementation requires strengthening the legal structure and legal culture